Improving the Assembly Time of a Plate Cover Product Through Fixture Design - Prianto, Bayu; Haryudiniarti, Ayu Nurul; Widodo Gustany, Eko; Restuasih, Sinta; Zulhamidi (Journal of Global Engineering Research and Science, 2024)
The welding process of a plate cover component in PT MCM has traditionally relied on manual methods, resulting in prolonged assembly time, inconsistent dimensional accuracy, and high operator dependency. To address these inefficiencies, this study proposes the design, fabrication, and implementation of a specialized welding fixture aimed at improving assembly time and product consistency. The research use an applied experimental methodology, start with the identification of production requirements through direct observation, interviews the operator, and document analysis. The fixture design was focus on principles of quick setup, structural stability, manufacturability, and safety standards. Technical modeling was performed using AutoCAD, then prototype fabrication using SPHC steel sheets (2 mm and 3 mm). The steel sheets shaped via precision laser cutting and assembled through MIG welding. The fixture was tested under real production conditions to evaluate its impact on setup time, weld quality, and geometric precise. Empirical observations revealed a significant reduction in average assembly time from 11.07 minutes to 8.46 minutes per unit. It's an improvement of approximately 2.61 minutes or 23.59%. Besides that, the fixture enhanced dimensional accuracy and reduced human error, its potential for broader implementation in similar manufacturing contexts. The results stated that fixture system has the critical role in improving process efficiency and product quality. It's feasible to apply in small and medium manufacture that seek transition from manual to standardized production workflows.